EVIDENCE AGAINST A CONTRALATERAL COATS PHENOTYPE BY OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 6 (22nd June 2022) - Daruich, Alejandra; Zola, Marta; Elalouf, Martine; Munier, Francis L.
Abstract : The foveal avascular zone is enlarged, and vascular density is decreased in affected eyes with Coats disease compared with fellow eyes, but no differences are seen between fellow and control eyes, confirming the unilateral nature of the disease. Abstract : Purpose: To evaluate the laterality of Coats disease by analyzing optical coherence tomography angiography features in affected, fellow, and control eyes. Methods: Patients with Coats disease who underwent optical coherence tomography angiography were retrospectively reviewed. Healthy eyes of age-matched patients served as controls. Automated optical coherence tomography angiography determination of foveal avascular zone size and vascular density of superficial capillary plexus and deep capillary plexus was recorded. Results: Thirty-four patients with Coats disease (13 with bilateral optical coherence tomography angiography) and 24 controls were included. The foveal avascular zone was larger in affected eyes compared with fellow eyes ( P = 0.004). Vascular density was decreased in affected eyes compared with fellow eyes in the superficial capillary plexus and deep capillary plexus whole images ( P = 0.047 and P = 0.007) and in the deep capillary plexus at the fovea ( P = 0.001). Vascular density was significantly reduced only in the deep capillary plexus in Stage 1 or 2A patients but in both plexuses in patients with Stage 2B1. No differences were shown on foveal avascular zone and vascular density values between fellow eyes of patients with Coats disease and controls. Conclusion: The foveal avascular zone is enlarged, and vascular density is decreased in affected eyes with Coats disease, but no differences are seen between fellow and control eyes, confirming the unilateral nature of the disease.